“Familias monoparentales y personalidad en los adolescentes de bachillerato de la Unidad Educativa José María Román”. Riobamba. Octubre 2017- marzo 2018. - Córdova Serrano, Tania Carolina (2018)
The objective of the present research was to determine single-parent families and personality in high school teenagers of the Unidad Educativa “José María Román". Period October 2017 - March 2018; it was identified the number of single-parent families that exist in a chosen course, taking into account that over the years, families experience changes in their structure, it means that it is related to the development of personality traits of the teenagers Methodologically, the research design is non-experimental, the level is descriptive and correlational, the population that was worked with was the high school students of the Unidad Educativa "José María Román" the sample was not probabilistic because its sampling was intentional. , which is made up of 38 students who attend the second year of high school, it was worked with 15 students from single-parent families, the ad hoc survey was used as a technique, it identifies if a student comes from a single-parent family; it was also used the Cattell questionnaire that identifies personality traits in a general way, in conclusion it was determined that statistically, individuals from a single parent family have no direct relationship with personality.